Best practices and practical strategies for co-designing virtual reality with Indigenous peoples: A scoping review protocol - Lillian Hung; Lenny Fisher; Jeffrey Wong; Yong Zhao; Katrina Yuen; Lily Haopu Ren (PLoS ONE, 2025)
Virtual reality (VR) is gaining traction in healthcare, education, and cultural sectors, from simulations in medical education to immersive museum experiences. Recently, VR has emerged as a powerful tool for Indigenous cultural preservation, language revitalization, and storytelling, offering immersive ways to safeguard knowledge and strengthen community connections. However, despite VR’s potential to support Indigenous self-determination, little is known about the extent of Indigenous leadership, engagements, and settler-Indigenous collaborations in VR development. There is a critical need to examine how VR can be ethically and meaningfully co-designed with Indigenous communities to ensure cultural integrity, respect for Indigenous knowledge systems, and equitable participation in technological innovation. Thus, this scoping review aims to identify practical strategies and best practices for co-designing VR with Indigenous communities. In accordance with the JBI methodology, we will conduct a comprehensive search across seven electronic databases, including MEDLINE (EBSCOhost), Scopus, Web of Science, ACM Digital Library, IEEE Xplore, Compendex (Engineering Village), and ProQuest Dissertations and Theses Global (ProQuest). Google Scholar will also be searched for grey literature sources. Eligible studies will focus on Indigenous populations (Population) and fully immersive VR co-design (Concept) across various contexts. Studies that do not discuss the design process will be excluded. Two independent reviewers will conduct literature screening, data extraction, and analysis, with findings synthesized narratively and presented in a structured charting table. The results will be disseminated through a peer-reviewed journal publication and shared with relevant community partners to support knowledge translation and application.